Antibacterial Activity Of Clay Mask From Houttuynia Cordata Leaves Extract Against Staphylococcus Aureus - Rahardhian, Muhammad Ryan Radix (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2024)
Facial skin that often looks dull and not glowing can be caused by the accumulation of dead skin cells. The solution to this problem is to exfoliate using a scrub. The content of secondary metabolites in Amis-amisan leaves (Houttuynia cordata Thunb) has antibacterial activity. This study aimed to determine the antibacterial activity of the face scrub ethanol extract of amis-amisan leaves against Staphylococcus aureus. The extract was obtained using the remaceration method using 96% ethanol. Concentrations of face scrub are 10%, 20%, and 30%. Antibacterial activity using the pour plate method. The results antibacterial activity of face scrub with concentrations of 10%, 20%, and 30% are 1.127 cm, 1.282 cm and 1.460 cm, respectively. The best antibacterial activity is a 30% concentration face scrub. The physical characteristics of the organoleptic, homogeneity, pH, spreadability, adhesion, and irritation tests of the face scrub meet the specified requirements.